Sources of ionizing radiation (IR) and their biological effects. An interdisciplinary view, from the physics to cell and molecular biology - Martinez Marignac, Veronica Lucrecia (2019)
Exposure to the IR is common to certain people like professionals handling radioactive materials or to the patients undergoing radio-diagnostics and radiotherapy or as millions of people who travel by air are exposed by X-rays scanning every day. Though it is indirect cause, IR may trigger mutation in healthy cells which further induces molecular alterations. It's known that ionizing radiation generates free radicals from cytoplasmic water and ultimately induces biomolecules lesions such as DNA damage. These damages may lead to neoplasm in normal and healthy cells however IR is not by itself a recognized and indisputable carcinogen present in the environment. In order to develop some type of cancer, they have to interact within the organisms and cells with other multiple factors of high complexity from physiological to environmental components (genetics of the living being, cellular microenvironment, epigenetic factors, environmental conditions, and others, perhaps still unknown). Here we discuss and present IR effect on living cells, ways of damage determination and compounds reported as radioprotectors.